A family of silatrane‐armed triazole‐encapped salicylaldehyde‐derived Schiff bases: Synthesis, spectral analysis, and antimicrobial and quantum chemical evaluation. (31st January 2017) - Singh, Gurjaspreet; Arora, Aanchal; Rani, Sunita; Kalra, Pooja; Aulakh, Darpandeep; Wriedt, Mario
Abstract : This work describes the successful synthesis of salicylaldehyde‐derived Schiff base‐linked organosilicon compounds following a highly efficient click approach. Hydroxyl‐terminated Schiff bases were alkylated to bis‐acetylenes (1 –3 ) which upon 3 + 2 cycloaddition with 3‐azidopropyltriethoxysilane yielded triazole‐decorated bis‐silanes (4 –6 ). These silanes further underwent base‐catalyzed transesterification to afford Schiff base‐linked triazole‐bound organosilatranes (7 –9 ). The final silatranes as well as precursor alkynes and silanes were comprehensively characterized using NMR ( 1 H and 13 C) and infrared spectroscopic techniques together with elemental analysis and mass spectrometry of compounds7 –9 . Also, the structures of alkynes1 –3 and silatrane7 were validated using single‐crystal X‐ray crystallography. Organosilatranes were initially screened for their pharmacokinetic profile using absorption, distribution, metabolism, excretion and toxicity (ADMET) tools and then explored for their antimicrobial activities, with compound9 emerging as the most potent antimicrobial agent. Compounds1 –3 and7 –9 also underwent thorough computational analysis by applying the density functional theory (DFT) approach with B3LYP/6‐31G(d) level of theory and the results were found to be consistent with the experimental data. Several DFT‐based descriptors were also evaluated providing a valuable insight into molecular stability and reactivity. Abstract : This work describes the synthesis of salicylaldehyde‐derived Schiff base‐linked organosilicon compounds following a highly efficient click approach. The compounds were well characterized using various spectral techniques and also single‐crystal X‐ray crystallography. The precursor diynes and final silatranes were also subjected to computational analysis. Organosilatranes were further explored for their photophysical properties and antimicrobial activities with compound9 emerging as the most potent antimicrobial agent.